Participation as a means-implications for intervention reasoning - Mats Granlund; Christine Imms (Frontiers Media S.A., 2024)
IntroductionThe increased focus among researchers and professionals on participation as an explicit intervention outcome has prompted a paradigm shift in both thought and practice. However, much research centers on altering participation outcomes in specific life situations and stages. This discussion paper considers "participation as a means" in pediatric rehabilitation and special education interventions, emphasizing its role in achieving lasting outcomes.MethodThis paper uses a Venn diagram approach to consider relations between three core concepts-participation, intervention, and outcomes-and their intersection. The paper's central theme revolves around the intersection of these concepts, wherein participation serves as a means to achieve enduring participation outcomes within the realms of rehabilitation and special education. The discussion is supported by contemporary empirical work and from literature identified in two recent scoping reviews focusing on the intervention process.ResultsAchieving enduring participation outcomes through participation in the intervention process necessitates creating a learning experience, with children and families actively participating in every step: identifying participation issues, seeking explanations, prioritizing intervention goals, selecting methods, implementing interventions, and evaluating the process and outcomes.DiscussionThis structured approach supports professionals and researchers to foster the skills and capacity required for lasting participation outcomes for children with impairments.